Strategi Pemeliharaan Hubungan Pada Pasangan Yang Menjalani Long Distance Relationship - Saniastari, Putu Yoni; Purnawan, Ni Luh Ramaswati; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2025)
A long-distance relationship is a romantic relationship where both couples are physically separate and therefore have limited communication. Living a long distance relationship is not easy because there are some limitations in making physical contact and hard to fulfill each individual's emotional needs. Good application of relational maintenance also takes many roles in maintaining long-distance relationships. Relational maintenance refers to individuals behavior to make an effort for maintain a relationship at some levels. This study aims to see if the relationship maintenance strategies are implemented using relational maintenance theory by applying qualitative research methods. Data collection techniques that used in this research are documentations and interviews to three infromans using Canary and Stafford's five-points relationship maintenance theory which are positivity, openness, assurance, networks and sharing task. The result showed that  the most effective way to maintaining long distance relationship is using openness and assurance strategies.